PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) MELALUI KEGIATAN OUTBOUND UNTUK MENINGKATKAN KEMAMPUAN KERJASAMA - Rini Yulitri; Wela Okta Putri; Ridwal Trisoni; Emeliya Hardi (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This research is motivated by the lack of optimal capacity for collaboration between children. One of the ways to improve the ability of child collaboration is by the Application of the Teams Games Tournament Cooperative Learning Model (TGT) through Outbound Activities. This study aims to determine the Application of the Cooperative Learning Model Type Teams Games Tournament (TGT) Through Outbound Activities Can Increase the Ability of Cooperation in the Kindergarten of Kasih IbuKoto Bangun. This study uses a quantitative approach with experimental methods, pre-experimental research design with type one group pretest-posttest design. The population of this study was all children in in the Kindergarten of Loving Mother Koto Bangun. Consists of 1 class with 10 children. The sampling technique is sampling saturation, namely children in group B, which amounted to 10 children. Data collection techniques used are observation and documentation. Based on the results of data analysis, the average pretest obtained is 32.6 and the average posttest results are 43.3. The results of the study show that the hypothesis is accepted with a significant level of 5%. Thus, there is a significant difference between pretest and posttest after treatment. Then the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected, meaning that the Application of the Cooperative Learning Model Type Teams Games Tournament (TGT) through Outbound Activities can Improve the Collaborative Ability in the Kindergarten of Kasih IbuKoto Bangun.